IDENTIFICATION OF GROWTH AND HINTERLAND AREA IN DEVELOPING NIAS DISTRICT - Yarman Gulo (Pusbindiklat - LIPI, 2015)
Growth center is the area or region that is growing very rapidly because it is used as a development central development affecting other areas in the vicinity. Given that areas be the center of that growth is expected in the surrounding areas also affected and stimulated to advance. The aim of the research was to identify subdistricts which have the opportunity or the potential to be the centers of economic growth in Nias District and to analyze the interaction (correlation) between growth center and the hinterlands of supporting subdistricts. The data were analyzed descriptive qualitatively, using skalogram analysis in order to know the centers of regional development based on the availability of economic, social, and governmental facilities and gravitation analysis in order to estimate the attraction of a location in the regional development, compared with the other locations or with the hinterlands. The result of the analysis showed that the first growth center in Nias District is Gido Subdistrict, the second growth center is Idanogawo Subdistrict, and the third growth center is Botomuzoi Subdistrict.